Graph Algorithms for Word Sense Disambiguation in Biomedicine - Goulart, Rodrigo; de Carvalho, Juliano; de Lima, Vera (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2015: Anais do XV Workshop de Informática MédicaDO - 10.5753/sbcas.2015.10365, 2015)
Word Sense Disambiguation (WSD) is an important task for Biomedicine text-mining. Supervised WSD methods have the best results but they are complex and their cost for testing is too high. This work presents an experiment on WSD using graph-based approaches (unsupervised methods). Three algorithms were tested and compared to the state of the art. Results indicate that similar performance could be reached with different levels of complexity, what may point to a new approach to this problem.